In Vitro Shoot Regeneration of Eucalyptus hybrid (Eucalyptus pellita Mueller x Eucalyptus brassiana Blake) - Tie, Tying Tying (Universiti Malaysia Sarawak (UNIMAS), 2008)
Eucalypt species are important in forestry both in the temperate and tropical regions. Through this study, shoot-tip and nodal explants were induced to develop multiple shoots by culturing them on MS medium supplemented with different concentrations ofBAP and NAA. After two weeks, the highest response of shoot multiplication was obtained in MS containing 0.05 mglL BAP in shoot-tip and O. IO mglL BAP in nodal explants. The regenerated plantlets were easily rooted on MS basal medium devoid of growth regulators. The rooted plantlets were acclimatized and planted out in the trays. The preliminary study of acclimatization has been successfully achieved within the time frame of this project. Apart from plant regeneration through proliferation of shoots, granulated calli were successfully induced by using juvenile explants and leaves of Eucalyptus hybrid. Callus was formed at the surface of the explant in all media tested. Calli were transferred to the same medium without growth regulators for further growth in dark. The cotyledon nodes and shoots tips cultured on B5 medium supplemented with 5 mgll 2, 4-D showed the highest callusing rates at about 78% for both explant type. Highest callusing rates of leaf explants was obtained in the presence of2.5 mgIL 2, 4-D, as approximately 100% of the leaf explants were induced to fonn callus on these media. The calli that formed from leaf explants were yellow in colour and harder. The callus was transferred separately to the MS medium containing various concentrations of BAP to induce the development of somatic embryos. No callus was fanned on leaf explants cultured on MS medium supplemented with BAP alone or BAP and NAA due to severe browning problem.